Administration of Corosolic Acid Decreased MDA, HMG-CoA, Through Increased Leptin and GLP-1 Levels in Obese Male Rats - Fransiska Mochtar; Wimpie I. Pangkahila; I Gusti Ayu Sri Mahendra Dewi; Made Ratna Saraswati; Norma Nur Azizah (Asian Journal of Social and Humanities, 2023)
Obesity is a condition where excessive fat is accumulated, which poses a health risk. Several treatments for obesity have been carried out, ranging from lifestyle adjustments to medication to surgery. Corrosolic acid (CA) is a natural compound that has the potential to act as an obesity agent through many mechanisms, including through reactive oxygen species (ROS). This study aims to prove that CA can reduce MDA levels and HMG-CoA reductase levels and increase leptin levels and GLP-1 levels in male Wistar rats with obesity. Wistar obese rats were orally treated with CA compound induction at a dose of 10 mg/Kg BW. MDA, HMG-CoA reductase, leptin and GLP-1 levels were examined using serum and plasma from mice in both groups of mice before and after treatment, using the ELISA method. CA to the treatment group can reduce the body weight of rat MDA levels significantly at p<0.0001, HMG-CoA reductase levels significantly at p<0.0001 and increase leptin and GLP-1 levels significantly at p<0.0001. CA's mechanism for treating obesity is through the ROS mechanism because CA has antioxidant levels that can capture free radicals in the body.CA has been proven to be an alternative drug in treating obesity by reducing body weight, MDA, and HMG-CoA levels and increasing leptin and GLP-1 levels in obese Wistar rats.